Legality of the Use of Autonomous Weapons Systems in International Humanitarian Law - Bobi Ardiansyah (Dinasti Research, 2025)
Along with the development of the era, the world of weapons has increased until a system called Autonomous Weapons Systems was created which allows weapons to be able to determine and take action completely without human intervention. Autonomous Weapons Systems are feared to violate International Humanitarian Law. This study uses a normative legal research method that refers to positive law to be able to analyze a problem being studied, especially in the realm of international humanitarian law. This research was conducted with a literature study, where the author examines several legal materials such as primary, secondary, and tertiary legal materials used based on the problem. The results of the study indicate that the use of Autonomous Weapons Systems in armed conflict or war is something that is legally valid as long as it does not violate the international law that regulates it and must be in line with International Humanitarian Law. Countries and Individuals in the use of Autonomous Weapons Systems can be held accountable for Violations of International Humanitarian Law